2007
DOI: 10.1038/sj.jp.7211664
|View full text |Cite
|
Sign up to set email alerts
|

Movement, imaging and neurobehavioral assessment as predictors of cerebral palsy in preterm infants

Abstract: Objective: To study the relative efficacy of three early predictors of cerebral palsy.Method: One Hundred and thirty infants with birth weight <1500 g were recruited. Video recordings of spontaneous general movements were made at 36 and 52 weeks postconceptional age. Magnetic resonance imaging and the neurobehavioral assessment of the preterm infant were done at 36 weeks postconceptional age. Follow-up neurological examination and Bayley assessments were made at 18 months corrected age to make early identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 21 publications
4
45
0
9
Order By: Relevance
“…These findings corroborate a study 24 that used the NAPI neurobehavioural assessment. In the mentioned study, the authors found that in variables such as alertness and orientation, motor development and vigour and irritability, the delay in the items related to alertness and orientation was higher in the infants who developed cerebral palsy and had sequelae than in those who did not have any motor sequelae.…”
Section: Another Studysupporting
confidence: 81%
See 1 more Smart Citation
“…These findings corroborate a study 24 that used the NAPI neurobehavioural assessment. In the mentioned study, the authors found that in variables such as alertness and orientation, motor development and vigour and irritability, the delay in the items related to alertness and orientation was higher in the infants who developed cerebral palsy and had sequelae than in those who did not have any motor sequelae.…”
Section: Another Studysupporting
confidence: 81%
“…The validity and sensitivity of the NAPI are described using an index of neonatal clinical complications. The inter-rater reliability coefficient ranges from 0.67 to 0.97, sensitivity (75%) and specificity (69%) 24 .…”
Section: Neurobehavioral Assessment Of Preterm Infants (Napi)mentioning
confidence: 99%
“…Few studies have examined very early neurodevelopment prior to term-age [21][22][23][24]. The Neurobehavioral Assessment of Preterm Infants (NAPI) evaluates the neurodevelopment of preterm infants at b37 weeks of post-conceptional age, with predictive power for later development until the first 3 years of age and the early detection of cerebral palsy in combination with magnetic resonance imaging [22,25].…”
Section: Introductionmentioning
confidence: 99%
“…The major consequences of this injury are permanent motor impairment (i.e., cerebral palsy [CP]) ranging from mild to profound spastic motor deficits [8][9][10][11][12][13], as well as a broad spectrum of cognitive, social behavioral, attentional, visual, and learning disabilities that manifest by school age in 25 to 50% of children [14][15][16][17][18]. In preterm survivors, magnetic resonance image (MRI)-defined WMI, but not gray matter injury manifests in the first months of life as abnormal movements that are predictive of CP [19][20][21]. The impact of WMI can be appreciated from a recent large population-based study of children with CP.…”
mentioning
confidence: 99%